Perancangan dan Pembuatan Sistem Informasi Pemesanan dan Pembayaran Tiket Pada Terminal Terpadu Pulo Gebang Berbasis Web - Prana, Dien Dinu (PT. Banjarese Pacific Indonesia, 2024)
Currently services at Integrated Terminal Pulo Gebang has no online ticket booking so it requires customers to came directly to the counter. That way there can be loss of booking data, double data. And the report on the number of passengers is still done manually, So that the impact that occurs is that the report on the company becomes unbalanced with data in the field. From the description of the problems that occur, it is designed and Built a Ticket Booking and Payment System in the Terminal Web-Based Integrated Pulo Gebang that is expected to solve problems that exists. For system modeling using tools, namely Unfield Modelling Language (UML) to create a Use Case Diagram, Actifity Diagram, Class Diagram. The Ticket Booking and Payment System at the Web-Based Pulo Gebang Integrated Terminal uses PHP and My SQL as its database language.